Difficultés De Mise En Œuvre De La Continuité Didactique Mathématique-Mécanique Au Secondaire Collégial, Registre Sémiotique Et Transfert Comme Éléments D’analyse - Raouf, Khadija; Radi, Mourad; Belazzaar, Imad; Talbi, Mohammed; Moussetad, Mohamed (European Scientific Journal, ESJ, 2016)
This article deals with the numerous pedagogical and didactic constraints to the transdisciplinary knowledge transfer between mathematics and physics (mechanics) at the last year of secondary school. By taking into consideration the three entities of the didactic triangle (Content, students and teachers), we analyzed in this exploratory study official pedagogical orientations, curricula and textbooks of mathematics and physics. Then, we administered to a sample of 12 to 15-year-old pupils, mathematical and physical written questionnaires in which they have to use proportionality/linearity concept by considering different register of semiotic representation and the rationality frame of each discipline., the analysis of the results reveal some difficulties that can be explained by a lack of knowledge related to the change of rationality frame and semiotic register rules. In order to understand the origin of these difficulties, we proceeded by analyzing the transdisciplinary practices of mathematics/physics teachers by means of a written semi-open questionnaire whose results highlight interdidactic rupture between mathematics and physics. To remedy that, we propose some strategies and possible lines of actions.